Traumatic Effects of War on Women in Alexievich’s The Unwomanly Face of War - Zahra Haghshenash (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This interdisciplinary study discusses Svetlana Alexievich’s The Unwomanly Face of War, a literary work that focuses on the history of World War Two from the perspective of female soldiers of the Soviet Union.  The women are veteran soldiers, a part of war history who continue their lives after the war and who suffer various mental disorders as a result of the war. These mental disorders are not only the aftereffects of the war, but also the consequences of political and social taboos of the Soviet Union. We analyze the women’s testimonies as they pertain to Cathy Caruth’s trauma theory. By analyzing trauma theory as it applies to the female soldiers, we see that if the society were to treat the female soldiers as heroines, to treat them with the same respect with which male soldiers are treated, the women would suffer fewer psychological disorders, but unfortunately, many of them suffer from Post-Traumatic Stress Disorders (PTSD).  Trauma theory draws on psychoanalysis to establish a connection between the characters in the novels and real-life people, allowing a consideration of each character as a more well-rounded and in-depth individual, improving the studies of both literature and psychology.